Analisis Penerapan Metode Six Sigma Untuk Meningkatkan Kualitas Gula Di Pt. Pabrik Gula X - Isa Abdussalam; Minto Waluyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT. PG X is part of ID FOOD which focuses on the sugar cane agro-industry sector. SHS sugar is the main product. To ensure production meets consumer standards and expectations, it is necessary to implement quality control during the production process. This involves quality control, improvement and improvement of systems so that the products produced are superior and competitive. In writing this article, the author is interested in exploring the problem of product defects and deviations in the production process, including defective products, as well as efforts to improve and improve product quality. The problem solving method used is the six sigma method. From the research results, it was found that the total production produced during October was 48,611 and 3,283 defective products were found. In the sugar production section, PT X Sugar Factory has a sigma level of 3.7 with a possible damage of 24,635 for one million production (DPMO).